Kandungan Logam Berat Pb dan Fe pada Air, Sedimen, dan Kerang Hijau (Perna viridis) Di Sungai Tapak kelurahan Tugurejo Kecamatan Tugu Kota Semarang - Pratama, Aditya Gandhi; Pribadi, Rudhi; Maslukah, Lilik (977-2407769)
Tapak River in Semarang City District Tugu alleged to have received the negative impacts of disposal of industrial wastes, aquaculture activities, and the existence of settlements in the surrounding streams containing heavy metals and can degrade water quality. Heavy metals such as Pb and Fe into the aquatic environment will experience precipitation, dilution and dispersion, then absorbed by the organisms that live in these waters. When exposed to organisms, high concentrations of heavy metals can be toxic and tend to accumulate in vital organs. Accumulation may have an impact on the food chain that affect human health. This study aims to determine the content of heavy metals lead (Pb) and iron (Fe) in water, sediment, and mussels (breathing viridis) in the River District Tread monument city of Semarang. There are four stations are used as the sampling site. A station is located close to the highway, Station B is located close to the sewer plant, Station C is located close to residential area, and Station D is located at the mouth of the river. The results showed that the average value of the highest content of Pb in the water at station A (1.11 mg / l). The average value of the highest content of Fe in the water at Station B (1:33 mg / l). The average value of the highest content of Pb in the sediments at Station A (62.87 mg / kg). The average value of the highest content of Fe in the sediments at Station A (59232.37 mg / kg).